Motoneuron and sensory neuron plasticity to varying neuromuscular activity levels (corrected version) - Ishihara, A.; Roy, R. R.; Ohira, Y.; Edgerton, V. R. (Exercise and Sport Sciences Reviews, 2003)
The size and phenotypic properties of the neural and muscular elements of the neuromuscular unit are matched under normal conditions. When subjected to chronic decreases or increases in neuromuscular activity, however, the adaptations in these properties are much more limited in the neural compared with the muscular elements.